The dynamics of the Swedish biofuel system toward a vehicle fleet independent of fossil fuels - Sanches-Pereira, Alessandro; Gómez, M.F. (ELSEVIER SCI LTD, 2015)
The objective of this study is to present an analytical framework monitoring the development of the Swedish biofuels system, to evaluate its impacts on the achievement of 10% of renewable fuels by 2020, and to identify development patterns in order to establish a vehicle fleet independent of fossil fuels by 2030. The methodological approach relies on systems thinking approach and uses causal loops diagram as a guide to our analysis. The results show that policymakers have to decide among different pathways of growth based on internal- and external-resources of the Swedish biofuel system as well as to apply either supply or demand pressures onto the system in order to accomplish a vehicle fleet independent of fossil fuels by 2030.